(untitled) (Scientia Agricola, 2018)
The phenotypic and genetic analysis of apple (Malus × domestica Borkh) genotypes is essential for breeding species. Information on the morphology and genetic structure of apple offers significant help for germplasm maintenance and selection of suitable material to breed superior cultivars. This study shows the results of an investigation on the morphology and the genetic diversity for 19 apple cultivars, which are preserved in an ex situ collection in Naoussa, Central Macedonia, Greece. Information was recorded over a 5-year period for 47 traits describing plant morphology and phenotype, as well as leaf and fruit quality. Data were analyzed using the principal component analysis (PCA) method. The Euclidean distance metric and the Ward’s agglomeration method were used in an unsupervised hierarchical cluster analysis of all cultivars. The cultivars were grouped into four main clusters, suggesting that the characterized apple collection has a high potential for specific breeding goals. Furthermore, the cultivars were genotyped using seven microsatellite primers. Moderate levels of polymorphism were detected, and 38 distinctive alleles (5.4 alleles per primer pair) were identified. Both multivariate clustering approach (phenotypic data) and the genetic distance clustering approach (genetic data) grouped the apple cultivars according to their type. Hence, these data could be used for protection or patenting processes of existing or new apple cultivars carried out by the EU-Community Plant Variety Office.